1999
DOI: 10.1074/jbc.274.18.12730
|View full text |Cite
|
Sign up to set email alerts
|

DNA Aptamers Selected Against the HIV-1trans-Activation-responsive RNA Element Form RNA-DNA Kissing Complexes

Abstract: In vitro selection was performed in a DNA library, made of oligonucleotides with a 30-nucleotide random sequence, to identify ligands of the human immunodeficiency virus type-1 trans-activation-responsive (TAR) RNA element. Aptamers, extracted after 15 rounds of selection-amplification, either from a classical library of sequences or from virtual combinatorial libraries, displayed an imperfect stem-loop structure and presented a consensus motif 5ACTCCCAT in the apical loop. The six central bases of the consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 31 publications
1
76
1
2
Order By: Relevance
“…Several strategies have allowed for the identification of various ligands of TAR RNA (8)(9)(10)(11). A large field of investigation concerns RNA aptamers that specifically bind TAR, which potentially offer a good selectivity and affinity for the RNA target.…”
mentioning
confidence: 99%
“…Several strategies have allowed for the identification of various ligands of TAR RNA (8)(9)(10)(11). A large field of investigation concerns RNA aptamers that specifically bind TAR, which potentially offer a good selectivity and affinity for the RNA target.…”
mentioning
confidence: 99%
“…The TAR-DNA aptamer: a loop-loop interaction Footprint studies performed on TAR bound to different DNA aptamers confirmed the loop-loop interaction suggested by the complementarity of their loop sequences (7). Preliminary 1D NMR studies were performed on a 29 nt RNA (TAR-29) corresponding to the apical region of the wild-type TAR sequence known to retain complete biological activity in vivo (1).…”
Section: Resultsmentioning
confidence: 99%
“…All the DNA molecules identified at the end of this SELEX process displayed an imperfect stem-loop with a consensus sequence 5′-ACTCCCAT-3′ containing five bases complementary to the TAR loop sequence, suggesting the possible formation of a loop-loop interaction. In addition, D-04, the aptamer displaying the highest affinity among the selected candidate, exhibited a thymine residue in the upper part of the stem, which was suggested to form a single base bulge in a previous study (7). Such anti-TAR aptamers might be of interest for the control of HIV development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to the different geometry adopted by the RNA-RNA helices in the TAR-R06 complex and the DNA-RNA (looploop hybrid) and DNA-DNA (the aptamer stem) helices in the TAR-aptamer complexes. Interestingly, in vitro selection using an oligodeoxynucleotide pool against TAR RNA led to aptamers that also form kissing complexes with substantial differences compared to the selected RNAs (Boiziau et al, 1999). At high (10 mM) magnesium concentration, the loop of the best candidate DI-04 forms five base pairs with the TAR loop.…”
Section: Aptamers To the Tar Elementmentioning
confidence: 99%